Modified Beef Tongue Model for Fourth-Degree Laceration Repair Simulation. Issue 3 (March 2017) - Illston, Jana D.; Ballard, Alicia C.; Ellington, David R.; Richter, Holly E.
Abstract : BACKGROUND: An existing model for fourth-degree laceration repair uses beef tongue with plastic or vinyl tubing. This modified model substitutes beef tripe for the anal mucosa and chicken leg muscles for the anal sphincter muscle analogs to create a realistic model. METHOD: Tripe is tunneled through the body of the trimmed beef tongue and sutured like an ostomy to simulate the anal canal. The tongue is incised toward the tripe "anal canal." Chicken leg muscles are tunneled from the incision out to the cut edges of the beef tongue to create anal sphincter muscle analogs. Procedures can be repeated on the opposite side. Two double-sided models can be made per tongue. EXPERIENCE: The model can be refrigerated or frozen and thawed before use. A fourth-degree laceration can be cut immediately before use. Materials were obtained at a local supermarket for 5–7 per half-tongue, double-sided model. Residents responded positively to the model and stated that animal tissue provided realistic haptic simulation. CONCLUSION: The modified beef tongue model utilizing tripe and chicken leg muscles as anal mucosa and anal sphincter muscle analogs, respectively, provided excellent perceived haptic fidelity. Moreover, it is an innovative, inexpensive, and well-received teaching tool to augment resident education. Abstract : The modified beef tongue model with tripe and chicken components has excellent haptic fidelity and is an affordable teaching tool for obstetric laceration repair.Supplemental Digital Content is Available in the Text.